SUSTAINABLE MANAGEMENT OF MANGO HOPPER (AMRITODAS ATKINSONY LETH AND IDIOSCOPUS NIVEOSPARSUS LETH TOGETHER) BY USING INSECT GROWTH REGULATOR (IGR), BUPROFEZIN 25 SC - GHOSH, SUNIL KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
Mango, Mangifera indica L., a member of family Anacardiaceae, is an important commercial fruit of the tropical and subtropical regions of the world. The crop suffers regularly to a colossal loss due to ravages of pests, which is considered to be a serious threat to Mango industry. The most destructive insects are the mango hoppers which cause greatest damages to the mango inflorescences in India and Bangladesh. The present investigation was undertaken with a new insect growth regulator (IGR) Buprofezin 25 SC (Buprostar), a candidate product from Meghmani Organics Limited (MOL), Ahmedabad, India for control on mango hoppers (Amritodous atkinsoni Leth. and Idioscopus r !veosparsus Leth.), the predominant species in mango orchards of West Bengal, India. Imidachloprid 17.8 SL (0.0053%) and Profenophos 50 % EC (0.075%) were used as check. During the month of February hopper population on attaining 5 adults /10 nymphs per panicle were given 2 sprays at a fortnightly interval. Observation on mango hopper, natural enemies and phytotoxicity were recorded one day before spray and 1, 7 and 14 days after the spray under the present investigation. Imidacloprid 17.8% SL treatment resulted in the best suppression of hopper population (91.89 % suppression) over untreated control, closely followed by Profenophos 50 % EC (88.51 % suppression) and Buprofezin 25% SC (Buprostar) (85.22% suppression). Buprostar increased in the natural enemies' population in ranging from 3.85 to 7.8:, and is similar to untreated control (4.26 to 7.04 indicating Buprofezin 25SC safe to natural enemies. Whereas, Imidachloprid 17.8 SL and Profenophos 50 % EC are moderate to highly toxic to natural enemies of mango. Buprostar (Buprofezin) 25 SC at 0.05% gave more that 85% control of mango hopper and is safer to natural enemies of mango and has no adverse effect on mango leaves, flowers and fruits. Considering the moderate to higher efficacy as well as its low toxie°ity to natural enemies and minimum impact on human health, coupled with higher yield potentially insect growth regulators (IGR) can be incorporated in future IPM programme and organic farming in fruit cultivation.